Refeeding syndrome in catatonic schizophrenia - Supriya Agarwal (Journal of Mental Health and Human Behaviour, 2019)
Refeeding syndrome is an uncommon but potentially fatal condition. It occurs in a patient who consumes a large amount of calories over a brief period of time after a sustained period of starvation. This syndrome is characterized by a high risk of cardiovascular collapse secondary to electrolyte imbalance if left untreated or if there is a delay in the management. Psychiatric patients with a diagnosis of schizophrenia or severe depression are known to refuse food for a prolonged period of time, thus creating a malnourished or starved metabolic state. The purpose of this article is to bring an acute awareness and sensitize the fellow psychiatrists about refeeding syndrome, a likely fatal possibility in a starved or malnourished patient on refeeding. Prompt recognition and management in collaboration with medical colleagues can save the life of these patients.